Effect of intracanal medicaments on dentinal tubule penetration of root canal sealers: a confocal laser scanning microscopy study - Emre Bayram; H. Melike Bayram (BMC Oral Health)
Abstract Background This study investigated the effect of three intracanal medicaments on the penetration ability of three different root canal sealers using confocal laser scanning microscopy (CLSM). Materials and methods 120 extracted single-rooted human teeth were used. The crowns were removed, and each canal was prepared. The teeth were divided into four groups (n = 30): three medicament groups (calcium hydroxide (CH), triple antibiotic paste (TAP), and double antibiotic paste [DAP]) and one control group. 0.1% Rhodamine B was incorporated. After three weeks, the medicaments were removed, and then canals were filled with one of the following sealers: AH Plus, MTA Fillapex, and TotalFill (n = 10). Fluorescein dye was added to the sealers. Horizontal sections (1 mm thick) were taken from each canal’s coronal, middle, and apical portions. Samples were then viewed under CLSM. Statistical analysis was performed using Kruskal-Wallis and Mann-Whitney U tests. Results TotalFill exhibited the highest dentinal tubule penetration values across all root levels and medicament groups, followed by AH Plus and MTA Fillapex. However, these differences were not statistically significant (p > 0.05). All sealers showed greater penetration in the coronal third compared to the apical third. Conclusions Although intracanal medicaments did not significantly affect sealer penetration, TotalFill demonstrated more consistent penetration patterns regardless of the medicament used.